The Interaction between Load Circuits and Decision of Frequency for Efficient Wireless Power Transfer - Kazuya Yamaguchi (Institute of Advanced Engineering and Science, 2018)
This paper derives an expression of efficiency of wireless power transfer on a situation that there are two devices towards one AC power supply. The interaction between a power supply and load is paid attention on a conventional wireless power transfer system, in contrast, the interaction between loads must be taken account of on the situation too. This is attributed to a possibility that a load disturbs the energy transmitted from a power supply to another load. Moreover each load needs different frequency of power supply for the ideal transfer since they have different natural frequencies on many situations. This paper models a circumstance that there are a power supply and two loads with a state space equation, and proposes how to decide a frequency of power supply to realize efficient transfer for each load.